2018
DOI: 10.1177/0309524x18780378
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of methods for estimating atmospheric stability at two coastal sites

Abstract: Understanding the atmospheric stability conditions is important in order to obtain accurate estimates of the vertical wind speed profile. This work compares and evaluates common methods for estimation of atmospheric stability using standard meteorological mast observations. Atmospheric stability distributions from three different met-masts located at two coastal sites are calculated and compared. The atmospheric stability parameter, L is estimated using the bulk Richardson number, the surface-layer Richardson … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 36 publications
0
24
0
1
Order By: Relevance
“…The gradient method is due to the postulated thermal layering of the MABL also found by Argyle and Watson (2014) to be dependant on the measuring heights used. There is therefore a degree of uncertainty related to the stability analysis, at several sites the stability distribution was therefore compared to previous studies and showed reasonable agreement (Høvsøre: Peña et al 2016, Skipheia: Bardal et al (2018), FINO1 and FINO3: Argyle and Watson (2014)). The use of different measurement heights was in addition thoroughly tested at FINO1, FINO2 and Skipheia, and although the stability distributions showed variation, the same tendencies prevailed and the same conclusions were drawn regardless of the measurement heights used.…”
Section: Atmospheric Stability Calculationmentioning
confidence: 75%
“…The gradient method is due to the postulated thermal layering of the MABL also found by Argyle and Watson (2014) to be dependant on the measuring heights used. There is therefore a degree of uncertainty related to the stability analysis, at several sites the stability distribution was therefore compared to previous studies and showed reasonable agreement (Høvsøre: Peña et al 2016, Skipheia: Bardal et al (2018), FINO1 and FINO3: Argyle and Watson (2014)). The use of different measurement heights was in addition thoroughly tested at FINO1, FINO2 and Skipheia, and although the stability distributions showed variation, the same tendencies prevailed and the same conclusions were drawn regardless of the measurement heights used.…”
Section: Atmospheric Stability Calculationmentioning
confidence: 75%
“…The gradient method is due to the postulated thermal layering of the MABL also found by Argyle and Watson (2014) to be dependant on the measuring heights used. There is therefore a degree of uncertainty related to the stability analysis, at several sites the stability distribution was therefore compared to previous studies and showed reasonable agreement (Høvsøre: Peña et al (2016), Skipheia: Bardal et al (2018), FINO1 and FINO3: Argyle and Watson (2014)). The use of different measurement heights was in addition thoroughly tested at FINO1, FINO2 and Skipheia, and although the stability distributions showed variation, the same tendencies prevailed and the same conclusions were drawn regardless of the measurement heights used.…”
Section: Atmospheric Stability Calculationmentioning
confidence: 87%
“…A part of this study includes the investigation of the correlation between atmospheric stability and abnormal vertical wind profiles. The stability analysis was conducted using the Richardson number (Arya, 1988) to calculate the Obukhov length and subsequently dividing the occurrences into the 5 stability classes (very stable, stable, neutral, unstable, very unstable) using Obukhov length bins given by Bardal et al (2018). Certain sites in the analysis had ultrasonic anemometers which would have enabled a sonic method of stability calculation.…”
Section: Atmospheric Stability Calculationmentioning
confidence: 99%
“…A part of this study includes the investigation of the correlation between atmospheric stability and abnormal vertical wind profiles. The stability analysis was conducted using the Richardson number (Arya, 1988) to calculate the Obukhov length and subsequently dividing the occurrences into the 5 stability classes (very stable, stable, neutral, unstable, very unstable) using Obukhov length bins given by Bardal et al (2018). Certain sites in the analysis had ultrasonic anemometers which would have enabled a sonic method of stability calculation.…”
Section: Atmospheric Stability Calculation 30mentioning
confidence: 99%
“…The gradient method is due to the postulated thermal layering of the MABL also found by Argyle and Watson (2014) to be dependant on the measuring heights used. There is therefore a degree of uncertainty related to the 15 stability analysis, at several sites the stability distribution was therefore compared to previous studies and showed reasonable agreement (Høvsøre: Peña et al (2016), Skipheia: Bardal et al (2018), FINO1 and FINO3: Argyle and Watson (2014)). The use of different measurement heights was in addition thoroughly tested at FINO1, FINO2 and Skipheia, and although the stability distributions showed variation, the same tendencies prevailed and the same conclusions were drawn regardless of the measurement heights used.…”
mentioning
confidence: 90%